2013
DOI: 10.1080/02626667.2012.754545
|View full text |Cite
|
Sign up to set email alerts
|

European precipitation connections with large-scale mean sea-level pressure (MSLP) fields

Abstract: To advance understanding of hydroclimatological processes, this paper links spatiotemporal variability in gridded European precipitation and large-scale mean sea-level pressure (MSLP) time series using monthly concurrent correlation. Strong negative (positive) correlation near Iceland and (the Azores) is apparent for precipitation in northwest Europe, confirming a positive North Atlantic Oscillation (NAO) association. An opposing pattern is found for southwest Europe, and the Mediterranean in winter. In the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
0
29
1
Order By: Relevance
“…Correlation between precipitation and cyclone counts was highest during summer. This differs from Lavers et al (), who found that the relationship between mean sea‐level pressure (MSLP) and precipitation across northwest Europe (including the BI) was weaker in summer than in winter. One explanation for this discrepancy is that the storm track is known to be more spatially restricted in summer than winter over the northeast Atlantic (Mesquita et al , ).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Correlation between precipitation and cyclone counts was highest during summer. This differs from Lavers et al (), who found that the relationship between mean sea‐level pressure (MSLP) and precipitation across northwest Europe (including the BI) was weaker in summer than in winter. One explanation for this discrepancy is that the storm track is known to be more spatially restricted in summer than winter over the northeast Atlantic (Mesquita et al , ).…”
Section: Discussioncontrasting
confidence: 83%
“…Thus, where cyclone frequency is an important driver of precipitation totals, it is reasonable to expect that regions of significant correlations between rainfall totals and MSLP (which bare the imprint of depression passage) should be similarly constrained. The different period (1957–2002) and spatial resolution (2.5° × 2.5°) of the reanalysis dataset used by Lavers et al () could be another factor. In highlighting the importance of cyclones in driving high precipitation amounts over the BI throughout the year, our results agree with Murphy and Washington (), who, in all seasons, observed a cyclonic pattern in the correlation field centred on the BI when assessing the association between MSLP and the leading empirical orthogonal function of BI rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…The NAO is an important driver of hydrologic variability in many European regions (Pociask‐Karteczka, ), especially in autumn and winter. It has strong and opposite effects in Northern and Southern Europe, but tends to be less impactful in central regions, including France (Lavers et al, ). Beyond NAO, Renard and Lall () documented that no standard climate index delivered skillful predictions of autumn floods in Mediterranean France.…”
Section: Autumn Floods In Francementioning
confidence: 99%
“…However, SCIs also have limitations. For instance, they may focus on capturing a mode of climate variability that is not relevant for hydrologic predictands in the target study region (Lavers et al, 2013). The combined use of several SCIs should account for the fact that distinct SCIs may be strongly related to each other (e.g., Westra et al, 2008;Westra & Sharma, 2009;Westra et al, 2015).…”
Section: Hidden Climate Indicesmentioning
confidence: 99%
“…For seasonal and monthly rainfall and river flows there are strong positive correlations with the NAO in northern and western locations, especially during the winter half year (October–March), and with increasing altitude (Burt and Howden, ). These patterns weaken during the spring and summer away from the far northwest of Scotland, where extra‐tropical cyclones continue to influence the weather and river discharge (Burt and Howden, ; Lavers et al, ). In contrast, extreme floods in small mountain catchments tend to have a closer association with negative NAO index values (Macklin and Rumsby, ; Foulds et al, ).…”
Section: Rainfall Extreme Floods and The North Atlantic Oscillationmentioning
confidence: 99%